Methodological guide for teaching basic english I Unit. IV; theme: present continuous, affirmative and negative statement, talking abourt peoples clothing. - White, Kimberlay Dae. White, Claudia Diana (Bilwi :URACCAN, 2008)
It is of great concert formus as English teachers the way that english is being taught at different levels of education:Primary, secundary and university level
Incluye índice, bibliografía
Col. Tesis
Keywords: 1. METHODOLOGICAL GUIDE FOR TEACHING BASIC ENGLISH